ENVIRONMENTALLY FRIENDLY BIFUNCTIONAL MATERIALS BASED ON ZnO/NATURAL ZEOLITE FOR METHYLENE BLUE DYE REMOVAL IN WATER - Nugroho, Muhammad Garda; Putri, Bilgis Laily Pratama; Mukharomah, Nur Laili Alfiatin; Wibisono, Alvin Adrian; Nurherdiana, Silvana Dwi; Wafi, Abdul (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
The treatment of dye wastewater, particularly from the batik industry, poses significant environmental challenges. This study explores the potential of ZnO-coated clinoptilolite natural zeolite as a dual-functional material for efficient and eco-friendly wastewater treatment through adsorption and photocatalysis. This study employed various solvents, i.e., aquadest and ethylene glycol and different treatments of heating and sintering to ensure the ZnO-coated natural zeolite. The ZnO/zeolite composite achieved a dye degradation efficiency of up to 98.68% under UV irradiation within 90 minutes. Characterization through SEM, FTIR, and XRD analyses confirmed the successful synthesis and structural integrity of the ZnO/zeolite composite. We also conducted an analysis of operational costs and energy consumption associated with the use of these bifunctional materials. The results indicate that the potential for utilizing these materials as a treatment method is promising, given their ease of use and low energy consumption, and warrants further investigation.